Spontaneous preterm delivery and risk factors at Tribhuvan University Teaching Hospital - Manandhar, BI; Sharma, J; Gurung, CK (Journal of Institute of Medicine Nepal, 2007)
Background: Preterm delivery is one of the major health problems in both, developing and developed countries because it is associated with increased peri natal morbidity and mortality. Methods: This was an unmatched hospital based case control study. The cases were the postpartum women, who delivered after 22 weeks and before 37 completed weeks of gestation and the controls were those postpartum women, who delivered after 37 completed weeks of gestation. The estimated sample size for preterm delivery (case) were 64 and for term delivery (control) were 128, with case to control ratio being 1:2. Results: There total number of deliveries during the study period was 1192. Of the total deliveries, 64 spontaneous preterm deliveries and 128 term deliveries were enrolled for the study, giving the prevalence of spontaneous preterm delivery = 5.5%. The previous preterm delivery, urinary tract infections in the index pregnancy and heavy physical activity during pregnancy showed strong independent risk for preterm delivery. The adjusted odds ratio for previous preterm delivery was 13.13, 95% CI 2.48-69.8 and P-value = .003. Similarly, adjusted odds ratio for urinary tract infection was 7.6, 95% CI 1.2-47.3 and p = .028. The farmers carried highest adjusted odds ratio of 14.8, 95% CI 2.8 – 78.2 and p = .001 and the adjusted odd ratio for small- scale business- women was 8.0, 95% CI 2.18 – 29.4 and p = .002. Conclusion: The study concluded that previous preterm delivery, urinary tract infection and heavy physical activity during pregnancy were independent risk factors for preterm delivery. Key words: Preterm delivery, urinary tract infection, physical activity, pregnancy. The full text of this paper is available at Journal of Institute of Medicine website